A microprogrammed control path architecture for an embedded IEEE 1149.1 test coprocessor - José M. M. Ferreira (2014)
This paper proposes a test coprocessor for a 32-bitMicroBlaze CPU core. A microprogrammed architecture is usedto implement the coprocessor control path, offering a flexiblesolution that ensures a straightforward expansion of the testcommand set. The current version supports a set of SVF-likecommands that is able to control one built-in IEEE 1149.1boundary-scan infrastructure. The proposed test coprocessor isuseful in a wide range of online test applications, and namely inthe case of mission-critical embedded systems, where online faultdetection and diagnosis become particularly important.